Upaya Meningkatkan Hasil Belajar IPA Siswa Melalui Model Pembelajaran Kooperatif Tipe Jigsaw Di Kelas VI SDN 57/X Kampung Laut T.A 2020/2021 - Dasni Dasni (Departement of Mathematics Education, 2022)
This research is motivated by the low learning outcomes of students. This study aims to describe and obtain information on improving science learning outcomes through the Jigsaw type cooperative learning model. This research is classroom action research consisting of two cycles, each cycle consisting of two meetings. Each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class VI SDN 57/X Kampung Laut, totaling 24 people. This research was conducted in the even semester of the 2020/2021 academic year. Data collection techniques using tests, observations, and documentation. Data were analyzed using percentages. The results of the study show that the Jigsaw type cooperative learning model can improve science learning outcomes for sixth grade students at SDN 57/X Kampung Laut by giving praise.